ANALISIS PENERIMAAN PENGGUNA TERHADAP KEGUNAAN SISTEM PENCATATAN KESEHATAN DIGITAL DI UKS DENGAN METODE SUS - Riska Pradita; Retno Kusumo (LPPM Universitas Awal Bros, 2026)
One crucial component of the School Health Unit (UKS) program is the recording of medical records and the reporting of students' health conditions. Implementing digital health records in the UKS offers various benefits, such as facilitating the documentation of health screening results, immunization status, nutritional status, medical history, periodic health check-up results, and follow-up health services for students. Despite the ongoing advancement of health digitalization, the implementation of digital health records in UKS remains relatively limited due to constraints such as inadequate information technology infrastructure, low user competence in utilizing digital technology, and a lack of integration between school health data and the information systems of healthcare facilities. Given this context, it is important to conduct research on user acceptance regarding the utility of a digital health recording system for UKS using the System Usability Scale (SUS) method. The objective of this study is to analyze the level of student acceptance regarding the design of a digital health recording system for UKS. This study employs a descriptive quantitative method. The research was conducted at SMA Negeri Batam, involving 30 respondents who serve as UKS administrators at the school. Data collection methods included field observations and the distribution of questionnaires. The questionnaire was designed based on the SUS (System Usability Scale) method. Results: The